Development of a low-cost alternative for the monitoring of the ore hauling production indicators in small-scale mining. - Machado, Jaime Ijichi (2019)
Small and medium-sized mining companies represent an important part of a country\'s mineral economy. These businesses, although representative and numerous, have low investment potential in their development through new technologies. One of the problems small and medium mining companies face is the ore hauling production monitoring. This operation alone can make as much as 60% of the total operating cost due to intense fuel and tires consumption and represents more than a half of the greenhouse gases emission in a quarry. Aiming at this problem, this document purposes to answer the following question: Is it possible to monitor the production of ore hauling in a small-scale mining with a low-cost system? The results showed that yes, it is possible to monitor the production of ore hauling in a small-scale mining with a low-cost system, using off-the-shelf hardware, regular office software and low use of labor. The results were validated in a quarry located in São Paulo State, where a US$ 480 system presented consistent results, improvements in productivity and reduction in emissions of 33 t CO2 per year.